2020
DOI: 10.5713/ajas.19.0220
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dietary supplementation of autolyzed whole yeast and yeast cell wall products on broiler chickens

Abstract: Objective: This study evaluated the effect of yeast products on growth performance, visceral organ weights, endogenous enzyme activities, ileal nutrient digestibility and meat yield of broiler chickens fed diets containing autolyzed whole yeast (WY) and yeast cell walls (YCW) at varying levels of inclusion.Methods: Nine dietary treatments consisting of WY or YCW included at 0.5, 1.0, 1.5, or 2.0 g/kg diet and a control diet without yeast supplementation was used in the experiment. Each of the nine treatments w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 31 publications
6
32
0
Order By: Relevance
“…Interestingly, dietary YC supplementation significantly increased the activities of chymotrypsin and ɑ-amylase in duodenal chyme. These findings are similar to a previous study that showed yeast products—autolyzed whole yeast and yeast cell wall—can improve pancreatic function and increase digestive enzyme synthesis of broilers ( Ahiwe et al., 2020 ). These results indicated that YC supplementation improved the digestibility of the protein and starch components of the feed.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, dietary YC supplementation significantly increased the activities of chymotrypsin and ɑ-amylase in duodenal chyme. These findings are similar to a previous study that showed yeast products—autolyzed whole yeast and yeast cell wall—can improve pancreatic function and increase digestive enzyme synthesis of broilers ( Ahiwe et al., 2020 ). These results indicated that YC supplementation improved the digestibility of the protein and starch components of the feed.…”
Section: Discussionsupporting
confidence: 92%
“…Recently, YH has become a trending supplement in broiler feed and showed a potential approach in enhanced feed intake and reduced environmental pollution [ 21 , 22 ]. In this trial, we observed that dietary supplement with YH had linearly increased BWG of broilers which was consistent with Emmanuel et al [ 23 ] who noted that broilers fed yeast products as yeast cell wall (1.5 g/kg) and autolyzed whole yeast (2.0 g/kg) had increased the BWG during starter, grower, and finisher phases. Furthermore, Onifade, [ 24 ] reported that dried yeast containing S. cerevisiae had improved the BWG of broilers.…”
Section: Discussionsupporting
confidence: 91%
“…In the present experiment, the improvement of productive performance traits by dietary inclusion of S. cerevisiae in laying quails could be related to the influence on the gut health that led to better FCR. It has been reported that dietary supplementation of S. cerevisiae in the animal diets increased the activities of A-amylase, trypsin, and chymotrypsin in duodenal chyme that may result in higher protein digestibility and nutrient utilisation (Ahiwe et al 2020). Moreover, yeast is a rich source of nutrients and it may act as an efficient substrate for beneficial microorganisms, which leads to the increase in proliferation of these gut microbiota (Zhang et al 2005).…”
Section: Discussionmentioning
confidence: 99%